ON CONVOLUTION TRANSFORMS WHOSE INVERSION FUNCTIONS HAVE COMPLEX ROOTS - Hakobian, S. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
For convolution transforms it has been received inversion formula, when φ(x) L^2(-∞, +∞), and inversion functions E(x)=^∞_k=1(1- s^2a_k^2) have complex roots satisfying to conditions _k=1^∞<+∞, |a_k|≤π4.